The Apocrypha: a guide - Goff, Matthew J. (Guides to sacred texts, 2024)
"Many readers of scripture, particularly in North America, are not aware that a substantial number of books were removed from their Old Testament. These books, often known collectively as the Apocrypha, were considered scripture for centuries by Christians and for millions of Christians today still are. This book is an introduction to the Apocrypha. It discusses ancient and early modern disputes about scripture, providing context for the formation of the category "Apocrypha." Each chapter focuses on a specific book, examining its core themes and ideas, the historical context of its composition, and later reception. This book is designed to be read along with the texts of the Apocrypha themselves, as presented in the New Oxford Annotated Bible. This volume is written not primarily for scholars but rather anyone who would like to learn more about them"--